KERAGAAN EKONOMI USAHA PENGOLAHAN IKAN NOMEI (Harpadon nehereus) KERING DI KELURAHAN JUATA LAUT KECAMATAN TARAKAN UTARA KOTA TARAKAN - Reski Amalia Putri; Oon Darmansyah; Juliani (Jurnal Pembangunan Perikanan dan Agribisnis, 2023)
Reski Amalia Putri, 2022. Economic Performance of Nomei Fish (Harpodon neherus) Dried Processing Business in Juata Laut Urban Village, North Tarakan Sub-district, Tarakan. Supervised by: (1) Oon Darmansyah and (2) Juliani. North Tarakan, specifically in Juata Laut urban village, has a big potency to support the activity of dried Nomei fish (Bombay Duck) processing. The Nomei fish business players’ success in managing the business should pay attention to the expenditure for fulfilling the business feasibility. This study aimed to analyze the business profit, measuring the levels of BEP, RCR, and PP, and describe the driving and inhibiting factors as well as the solutions. This study was qualitative and quantitative using the census method as the sampling technique. The data analysis used in this study was the analysis of production costs and profitability, economic analysis of the business, descriptive analysis of driving and inhibiting factors, and the solutions. Based on the analysis result, the earned profit of Rp. 20,386,000/month, BEP price of Rp. 28,487/Kg, BEP production of 44,046 Kg/month, BEP selling of Rp. 919,753/month, RCR of 3,515, and PP of 0,637. The driving factors of the business were Nomei fish as the raw material available all year round to improve the value-added of the Nomei fish, and the primary business for communities in fish processing. Meanwhile, the inhibiting factors of the business included capital, weather, and dried Nomei fish sales. Keywords: Dried Nomei Fish, Profitability, BEP, RCR, PP, Driving and Inhibiting Factors